2020
DOI: 10.1139/cjas-2018-0237
|View full text |Cite
|
Sign up to set email alerts
|

Barley or black oat silages in feeding strategies for small-scale dairy systems in the highlands of Mexico

Abstract: High costs from external inputs in small-scale dairy systems (SSDS) and possible effects of climate change, require forage alternatives as silage for the dry season, from small-grain cereals that have short cropping cycles, winter hardiness, and good nutritional quality. The objective was to assess the provision of 10 kg dry matter (DM) cow−1 d−1 of barley (BLY) or black oat (BKO) silages in three treatments: T1 = 100% BLY; T2 = 50% BLY + 50% BKO; T3 = 100% BKO for milking cows. All treatments also received 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 30 publications
2
12
1
6
Order By: Relevance
“…Average enteric CH 4 emissions per year (kg CH 4 y −1 ) were higher than reported in dairy cows in Canada (118 kg/year) [ 45 ], but in terms of g CH 4 per day/cow, emissions were lower in dairy cows under rotational grazing in New Zealand (402 ± 52 g/day) [ 46 ], but similar results in Ireland (357.6 ± 4 g/day) [ 47 ] and also in intensive dairy farming in China (370 g/day) [ 48 ]. Regardless of management cut and carry or grazing (366 ± 2 g/day) was similar between treatments ( p > 0.05), being lower when using white clover (359.9 g/day) compared to red clover (372.7 g/day), the latter agrees with Carrillo Hernandez et al [ 23 ] who found that cows that grazed annual pastures emitted a higher amount of methane (266.6 g/day), compared to cows that grazed perennial pastures (242.6 g/day); hence, it is important to consider that depending on the type of forage, enteric fermentation and therefore methane emission will vary.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Average enteric CH 4 emissions per year (kg CH 4 y −1 ) were higher than reported in dairy cows in Canada (118 kg/year) [ 45 ], but in terms of g CH 4 per day/cow, emissions were lower in dairy cows under rotational grazing in New Zealand (402 ± 52 g/day) [ 46 ], but similar results in Ireland (357.6 ± 4 g/day) [ 47 ] and also in intensive dairy farming in China (370 g/day) [ 48 ]. Regardless of management cut and carry or grazing (366 ± 2 g/day) was similar between treatments ( p > 0.05), being lower when using white clover (359.9 g/day) compared to red clover (372.7 g/day), the latter agrees with Carrillo Hernandez et al [ 23 ] who found that cows that grazed annual pastures emitted a higher amount of methane (266.6 g/day), compared to cows that grazed perennial pastures (242.6 g/day); hence, it is important to consider that depending on the type of forage, enteric fermentation and therefore methane emission will vary.…”
Section: Discussionsupporting
confidence: 85%
“…In another study [21], carried out in dairy cows feed with Ryegrass grazing Festulolium associated with white clover, oat silage, and commercial concentrate, obtained similar milk yields (18.86 kg/d/cow) as in the present study. It is important to consider that under the conditions of the present simulation study, the predictions made with previous studies coincide [15,[20][21][22][23]26], considering that under SSDS systems, they are in the range of 14 to 20 kg milk production.…”
Section: Dmi (Kgmentioning
confidence: 69%
See 1 more Smart Citation
“…Among small-grain cereals with forage potential for SSDS there are: triticale, an intergeneric hybrid between wheat and rye which presents greater environmental tolerance and less nutrient loss as it matures (González-Alcántara et al, 2020; Haque et al, 2008;Harper et al, 2017); barley, with higher digestibility and microbial protein production reducing the need for protein sources, with greater competitiveness and dominance over other species (Baron et al, 2015;Gómez-Miranda et al, 2020); and rye, favoured for its resistance to drought, diseases and low temperatures (Castro et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that small-grain cereal grains have advantages for use as forage, due to their short agronomic cycle and higher resistance to dry conditions (Murillo et al 2001;Salgado et al 2013;Celis-Álvarez et al 2016;Gómez-Miranda et al 2020).…”
Section: Introductionmentioning
confidence: 99%